Compliance Audit Approach to Campaign Finance Reporting Among Regional Head Election Candidates in West Java Pilkada 2024 - Tommy Kuncara; Matsui Takayuki (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the compliance of campaign finance reporting among candidate pairs in the 2024 West Java regional head election (Pilkada) using a structured compliance audit approach. Campaign-finance compliance is critical for ensuring transparency, accountability, and public trust in electoral governance. The objective of this study is to assess whether mandatory reporting documents—LADK, LPSDK, and LPPDK—provide an auditable and consistent evidence trail. The study employs a quantitative document-based design using secondary data from official publications of the West Java Election Commission (KPU). The unit of analysis is each candidate pair at the provincial level. Compliance indicators are derived from PKPU No. 14/2024 and analyzed using descriptive statistics and indicator-frequency analysis. The findings reveal three key patterns. First, LADK reports show uniform zero opening balances, but early funding is highly concentrated and includes late submission cases. Second, LPSDK disclosures indicate varied funding structures (party-dominant, mixed, and individual-based), with multiple correction requirements. Third, LPPDK reports demonstrate high correction prevalence and very high spending ratios (98%–100%), resulting in minimal closing balances. These results suggest that compliance should focus not only on submission but also on auditability, including completeness, consistency, and traceability of financial data. This study contributes a replicable compliance-audit framework for evaluating campaign finance reporting and extends audit literature by emphasizing candidate-level reporting in subnational elections.